No-Touch Radio Frequency Ablation for a Subcapsular Hepatocellular Carcinoma: A Case Report and Review of Literature - Malla, Sundeep; Vaishnav, Manas; Shalimar, Shalimar; Madhusudhan, Kumble Seetharama (Journal of Clinical Interventional Radiology ISVIR, 2021)
Radiofrequency Ablation of subcapsular lesions poses a challenge due to the risks of tumour seeding along the track, hemorrhage and lower efficacy. “No touch ablation” is a relatively novel technique used in the ablation of subcapsular HCC with good results. This technique avoids direct puncture of the tumour by inserting more than one electrodes adjacent to and outside the tumor and activating them sequentially to perform ablation. The risk of track site seeding and haemorrhage is significantly reduced. We describe a case of a subcapsular HCC in a 65-year-old female patient which was successfully treated with this novel technique.
Keywords: radio frequency ablation; no-touch ablation technique; hepatocellular carcinoma